Strom und Vorurteil 52 weitgehend unkritische Kolumnen - Passig, Kathrin 1970- ([Verlag nicht ermittelbar], 2020)
The collection contains Kathrin Passig’s columns published in the weekend magazine of the German newspaper Frankfurter Rundschau in 2019. It is available in several versions, each of which is associated with different earning potential, as Passig explains on her website: "Available as Kindle e-book or paperback at Amazon, as e-book at Google Play (I get money). As EPUB at Library Genesis or here on my website (I don’t get money)" (Kathrin Passig, "Bücher"). The advantage of print-on-demand service providers like Amazon is mainly that the author doesn’t have to worry about distribution, shipping, and invoices herself. ...
Keywords: Künstlerbuch